Investigation of in-vitro antioxidant and cytotoxic activity of Blumea lacera leaf extract - Khan, Mujtaba Ali (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.